A strong magnesium oxychloride cement wood adhesive via organic–inorganic hybrid. (23rd August 2021) - Zhou, Wenguang; Ye, Qianqian; Shi, Sheldon Q.; Fang, Zhen; Gao, Qiang; Li, Jianzhang
Highlights: Simultaneously flame retarded, high bonding strength and formaldehyde-free adhesive was fabricated. A stable system of organic–inorganic hybridization was constructed. The wet shear bond strength of lap plate increased by 53.5%. Inorganic adhesive greatly reduced total heat release and total smoke production rate of wood-based composites. Abstract: Developing high performance and non-toxic adhesives to replace the petroleum-based adhesives are highly desirable for wood industry. The use of magnesium oxychloride cement (MOC) inorganic adhesive is beneficial for the protection of human health and conservation of fossil resources. However, the low initial viscosity and poor water resistance have limited their application in plywood fabrication. In this study, polyacrylamide (PAM) and sodium polyacrylate (PAAS) were added to the adhesive as organic agents to construct wood-based composites by the organic–inorganic hybrid strategy. The MOC would be solidified by a cold-pressing method, forming a formaldehyde-free wood adhesive with high bonding performance. The addition of PAM efficiently improved the stability and processability of MOC, while PAAS improved the water resistance of MOC by inducing Mg 2+ chelation and transforming the phase 5 structure. This adhesive exhibited a 53.5% increase in wet shear strength in contrast with the unmodified MOC adhesive. In addition, the MOC adhesive bonded wood-based composites showed high flame-retardant properties.